Transactional reading in EFL learning: a path to promoting critical thinking through urban legends - Leal Hernández, Mariela; Gómez Rodríguez, Luis Fernando (Colombian Applied Linguistics Journal, 2015)
This article reports an action-research study3 that attempted to develop EFL4 eleventh graders’ critical thinking through the transactional reading approach. Since learners were used to taking grammar-oriented English classes and had negative attitudes towards reading, they were encouraged to do reading transactions with the support of urban legends. These legends inspired them to discuss social conflicts (loss of values, drug consumption, alcoholism, risky lifestyles, etc.) that related to the problems of the insecure and vulnerable neighborhood in which they lived in Bogotá. Data were collected from teachers’ observations, interviews with students, and worksheets (artifacts) in a pedagogical intervention. Through the grounded approach analysis, it was found that learners fostered critical thinking as they criticized human behaviors, generated solutions to correct questionable behaviors, and produced knowledge based on previous information in the foreign language.